Neopsilotrema n. g. (Digenea: Psilostomidae) and three new species from ducks (Anseriformes: Anatidae) in North America and Europe - Kudlai, Olena; Pulis, Eric E; Kostadinova, Aneta; Tkach, Vasyl V (Systematic parasitology, 2016)
Neopsilotrema n. g. (Digenea: Psilostomidae) and three new species of psilostomid digeneans are described from birds in North America and Europe: Neopsilotrema lakotae n. sp. from Aythya americana (Eyton) in North Dakota, USA, Neopsilotrema affine n. sp. from Aythya affinis (Eyton) in Minnesota, USA and Neopsilotrema lisitsynae n. sp. from Anas crecca L. in Kherson Region, Ukraine. Neopsilotrema n. g. shares a bipartite seminal vesicle with only three genera within the Psilostomidae, Psilotornus Byrd & Prestwood, 1969, Psilostomum Looss, 1899 and Grysoma Byrd, Bogitsh & Maples, 1961. The new genus differs from Psilotornus in the presence of a muscular pharynx and a massive ventral sucker; the location of the cirrus-sac in relation to the ventral sucker and more posterior location of ovary; the nature of the vitellarium (i.e. comprising large, compact follicles with small vitelline cells vs weakly defined follicles with large vitelline cells); a proportionately shorter forebody; and in parasitisation in anseriform (vs passeriform) birds. Differences between the new genus and Psilostomum comprise the shape of the body, the relative size of the suckers, somewhat longer forebody and a more anterior location of the testes. Neopsilotrema n. g. differs from Grysoma in the relative size of the suckers, the degree of development of prostatic cells, the nature of the vitellarium and the size of the eggs in relation to body length. The European species Neopsilotrema lisitsynae n. sp. is distinguished from its congeners in having a longer, narrower and distinctly more elongate body with a longer post-testicular region and anterior limits of the vitelline fields posterior to ventral sucker. The two North American forms, Neopsilotrema lakotae n. sp. and Neopsilotrema affine n. sp., are cryptic species with largely overlapping metrical data; these are distinguished by comparing genetic data. The phylogenetic hypotheses for the Psilostomidae developed from sequence data analyses based on partial 28S rDNA support the erection of the new genus and the distinction of the three new species. Grysoma marilae (Price, 1942) agrees more closely with the generic diagnosis of Neopsilotrema, especially in relation to the size and shape of the body, the relative length of the forebody and post-testicular field, the structure of the vitellarium, the location of the reproductive organs and the sucker ratio. Consequently, it is here transferred to the new genus as Neopsilotrema marilae (Price, 1942) n. comb.
Keywords: druhová specificita; Ukrajina; Animals; RNA ribozomální 28S; kachny; Trematoda; Phylogeny; Molecular Sequence Data; molekulární sekvence - údaje; zvířata; North America; fylogeneze; RNA, Ribosomal, 28S; Species Specificity; Severní Amerika; Ukraine; Ducks